The Resocialization Dimension of Electronic Tagging as a Non-Custodial Model of Serving Deprivation of Liberty Sentences - Dariusz Sarzała (Maria Curie-Skłodowska University, Lublin, Poland, 2017)
In this paper pointed out the specific functioning of electronic surveillance in the Polish model legislation with special emphasis on the role of this system in the rehabilitation of people covered by it. This article aims to analyze aspects of the rehabilitation of electronic surveillance as an alternative to the currently dominant model of the insulation of imprisonment in a prison as a total institution. The author also pointed to the need to increase the efficiency of electronic surveillance by the introduction of treatment programs that increase the chance of a fuller social rehabilitation of people who are covered by this system.